Analisis Keadaan Stunting pada Kelompok Balita di Kecamatan Tukdana dengan Pendekatan Decision Trees - Asep Budiyanto; Dodi Solihudin; Ryan Hamonangan; Cep Lukman Rohmat; Ade Rizki Rinaldi (Universitas Wahid Hasyim, 2024)
The impact of stunting on babies is an important parameter for assessing the health and welfare of children in an area. Stunting, often triggered by demographic and health factors, has serious implications for children's physical and cognitive growth. This research aims to understand the impact of demographic and health factors on stunting in children in Tukdana District, Indramayu Regency. Through data analysis, factors such as maternal age, access to clean water, sanitation facilities, and baby weight and length status were identified as significant contributors to stunting. The Decision Trees method was used to identify factors that play a role in stunting in babies, with an accuracy rate of 95.43%. The implications of this research include planning more effective interventions to deal with stunting, both in Tukdana District and in similar areas in Indonesia. Even though the majority of babies in Tukdana District have good nutritional status, further monitoring and prevention efforts are still needed to ensure optimal nutritional well-being for them. In conclusion, this research highlights the importance of identifying factors that cause stunting in infants in Tukdana District, as a basis for planning more effective interventions.